Distributional Implications of Tax Evasion: Evidence from the Lab. (November 2014) - Doerrenberg, Philipp; Duncan, Denvil
We study the differential effects of tax reforms on actual and observed net income inequality in a laboratory experiment where participants first supply effort and then make a tax reporting decision. We show that for a group with relatively homogeneous levels of true gross income, higher taxes increase both actual and observed inequality but have a larger effect on actual inequality. We decompose the effect of tax rates into a mechanical tax effect and two behavioral (effort and evasion) effects. Our results indicate that the mechanical and effort effects on actual inequality are larger than on observed inequality while the evasion effect is generally larger on observed inequality. We also find that the size of the effects, relative to each other, depends on the measure of income.